The reflection of two past outbursts of Sagittarius A* observed by Chandra during the last decade. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Clavel, M.; Terrier, R.; Goldwurm, A.; Morris, M. R.; Ponti, G.; Soldi, S.; Trap, G.
Abstract: The supermassive black hole at the Galactic center, Sagittarius A* has experienced periods of higher activity in the past. The reflection of these past outbursts is observed in the molecular material surrounding the black hole but reconstructing its precise lightcurve is difficult since the distribution of the clouds along the line of sight is poorly constrained. Using Chandra high-resolution data collected from 1999 to 2011 we studied both the 6.4 keV and the 4–8 keV emission of the region located between Sgr A* and the Radio arc, characterizing its variations down to 15″ angular scale and 1-year time scale. The emission from the molecular clouds in the region varies significantly, showing either a 2-year peaked emission or 10-year linear variations. This is the first time that such fast variations are measured. Based on the cloud parameters, we conclude that these two behaviors are likely due to two distinct past outbursts of Sgr A* during which its luminosity rose to at least 10 39 erg s −1 .